Impact of team Work on developing organizational trust: A case study ‎of the Faculty of Economic and Commercial Sciences and Management ‎Sciences at Laghouat University - BenbertalAbdelkader ‎ (Dirassat Journal Economic Issue, 2018)
The paper aimed to study the impact of the team work on the development of organizational trust, case study of the professors of the Faculty of Economic and Commercial Sciences and Management Sciences in university "Amar Thelidji" Laghouat, a sample of 48 out of 124 single professor composed macro community, The study found the following: Most of the faculty professors exercising a lot of tasks in the form of team work; Acceptable level of organizational trust among professors towards colleagues and supervisors; There is statistical significance of the impact of the team work on the organizational trust, in addition to the estimated correlation (0.54) and the change in organizational trust is interpreted by the work team at 30%.